2021
DOI: 10.1136/bmjebm-2021-111667
|View full text |Cite
|
Sign up to set email alerts
|

Association of study design features and treatment effects in trials of chronic medical conditions: a meta-epidemiological study

Abstract: ObjectivesTo evaluate the association of study design features and treatment effects in randomised controlled trials (RCTs) evaluating therapies for individuals with chronic medical conditions.DesignMeta-epidemiological study.SettingRCTs from meta-analyses published in the 10 general medical journals with the highest impact factor published between 1 January 2007 and 10 June 2019 and evaluated a drug, procedure or device treatment of chronic medical conditions.Main outcome measuresThe association between trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…We included eight meta-epidemiological studies in our review (Figure 1, Supplementary file B). [10][11][12][13][14][15][16][17] The eight meta-epidemiological studies were published between 2013 and 2021 (Table 1) and investigated a total of 264 meta-analyses (range 12-86) and 2725 trials (range 82-1098). All eight meta-epidemiological studies investigated meta-analyses and trials from specific clinical areas (e.g., critical care and neonatal care).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We included eight meta-epidemiological studies in our review (Figure 1, Supplementary file B). [10][11][12][13][14][15][16][17] The eight meta-epidemiological studies were published between 2013 and 2021 (Table 1) and investigated a total of 264 meta-analyses (range 12-86) and 2725 trials (range 82-1098). All eight meta-epidemiological studies investigated meta-analyses and trials from specific clinical areas (e.g., critical care and neonatal care).…”
Section: Resultsmentioning
confidence: 99%
“…Commercially funded trials frequently have surrogate primary outcomes 28 . In contrast, four of the included meta‐epidemiological studies (154 meta‐analyses of 1613 trials) mainly included meta‐analyses with mortality outcomes 10,12–14 . The trial outcomes included in the meta‐analyses may therefore in some cases be secondary outcomes not used for framing trial conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed literature search and method of study selection and data extraction were reported in a previous study 12. The same database has been used in a previous publication, while the current manuscript intends to address different objectives 13 14. With different inclusion/exclusion criteria and updated literature search till 10 June 2019, different datasets were included in the analyses.…”
Section: Methodsmentioning
confidence: 99%